Effect of aid for trade policy and regulations on tariff policy volatility: Does institutional and governance quality matter? - Sèna Kimm Gnangnon (Economies, 2019)
This article investigates empirically the effect of aid for trade policies and regulations on the volatility of tariffs in the recipient countries. The analysis has used an unbalanced panel dataset of 107 countries over the period from 2002 to 2015. The empirical results, based on the two-step system Generalized Methods of Moments (GMM) approach, show that aid for trade policies and regulations influences negatively and significantly tariff policy volatility in recipient countries. Additionally, the findings indicate that the better the institutional and governance quality in recipient countries, the higher is the reducing effect of aid for trade policies and regulations on tariff policy volatility. These results, therefore, suggest that a scale up of aid for trade policies and regulations to, inter alia, build the capacity of policymakers in recipient countries to contribute to reducing tariffs volatility in these countries, which would, in turn, likely benefit donor countries. Furthermore, improving domestic institutions and governance in recipient countries would further enhance the reducing impact of this aid on tariff volatility, which, once again, benefits both the recipient countries and donor countries.
Keywords: F14; F35; 330; aid for trade policies and regulations; tariff policy volatility